PEMBEKALAN KESUKSESAN WIRAUSAHA WANITA PADA UKM KERAJINAN DI SERANG - Hidayah, Nur; Caroline, Angelica; Bakti, Kevin Karunia (Transpublika Publisher, 2022)
The purpose of Student Creativity Program (PKM) activities is to provide knowledge about the success of women's entrepreneurs, related to things that need to be considered for women entrepreneurs in increasing their success in entrepreneurship. Partners that are used as a place of activity are SMEs which are engaged in the manufacture of handicrafts from knitting and mute threads. The name of this business is known as “Mada Mute”. The business location is located in Serang city, Banten province. PKM activities are based on initial observations of partners. Partners have not received a briefing of knowledge about things that partners need to pay attention to in improving entrepreneurial success. The method offered in this activity is through an online ZOOM meeting, assisted by two students as hosts. The results of the activity show that the training activities have been carried out smoothly, partners are enthusiastic in understanding the material presented by the chairman, and the results of the evaluation show an increase in partners' knowledge about entrepreneurial success as a provision for running a business.